A retrospective study of histologically diagnosed intra-oral lesions within Ugu district, KZN, South Africa - Reddy, Larisha Yashoda (University of the Witwatersrand, Johannesburg, 2023)
Introduction: The oral cavity is exposed to a magnitude of physical and chemical trauma, carcinogenic agents and microbial pathogens that may cause a wide spectrum of oral lesions. These oral lesions may appear as benign, potentially malignant, or malignant thereby requiring biopsies to determine histopathological features to confirm a diagnosis. Oral lesions have the potential to hinder the quality of life for the afflicted patient. The patients’ speech, mastication, swallowing may be affected with the occurrence of oral dysesthesia. With the confirmation of a positive malignant biopsy, the afflicted individual will have to endure the possible side effects of chemotherapy and radiation. In global studies, the prevalence of oral lesions may vary amongst different countries, geographical areas, ethnicities, cultural practices, and social habits. Aim: To identify the different types of intra-oral lesions and the prevalence of malignant oral lesions within UGU district, Kwa- Zulu Natal (KZN). Objectives: 1. To identify the different types of intra oral lesions and characterise by demographics. 2. To determine the prevalence of malignant oral lesions within UGU district, KZN. 3. To determine the association between patients’ social habits and the development of the most common intra oral lesions, with the differentiation of malignant vs non-malignant oral lesions. 4. To assess the concordance of a clinical differential diagnosis and histopathological diagnosis. Study design and Methodology: A quantitative, retrospective case review of dental patient files and histopathological reports of the four selected hospitals in UGU were analysed from January 2016 to August 2022. One hundred and thirty-four patient records were reviewed. Data collected included patients’ age, gender, comorbidities, social habits, differential diagnosis, and histological diagnosis. The data was analysed using a free open-source statistical software program called “R”. Study results: One hundred and thirty-four patients met the criteria of this study. The age of patients ranged between seven and eighty-seven (M= 46.37; SD= 20.77). There were 81 females (60.4%) and 53 males (39.6%). Benign lesions had represented 67.2% (N: 90) of the intra oral biopsies, with the remaining 32.8 %, (N:44), representing malignant lesions. The most common lesions presenting in UGU district were fibrous epulis (N: 15, 11.2%), pyogenic granuloma (N:36, 26.9%) and squamous cell carcinoma (N:37, 27.6%). No statistical relation was proven between ethnicity, sex, and social habits with the benign lesions of fibrous epulis and pyogenic granuloma. Statistical relation was proven between squamous cell carcinoma and ethnicity, gender, and social habits. A substantial level of concordance (agreement) was proven with the Kappa Statistic of 0.7437, hereby indicating a good general knowledge of intra-oral lesions amongst the dentist performing the intra oral biopsies within UGU district. Conclusion: Fibrous epulis, pyogenic granuloma and oral squamous cell carcinoma had been identified as the three most common lesions in UGU, KZN, representing 65.7% of the confirmed biopsy results. Fibrous epulis and pyogenic granuloma had shown no statistical association to ethnicity, gender, alcohol consumption and smoking. In this study, oral squamous cell carcinoma had shown statistical association to white males and consumption of alcohol and smoking. This study has demonstrated the diversity and prevalence of intra-oral lesions within the rural district of UGU, KZN, South Africa as compared to global studies.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Dentistry, (Maxillofacial and Oral Surgery), to the Faculty of Health Science, School of Oral Health Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Intra-oral lessons; Histology; Histologically; Diagnosed; Retrospective study; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education